Optimization of meat-containing semi-finished products formulations with the microbiological derived proteases application - Pasichnyi, Vasyl; Shvediuk, Dmytro (My University, 2019)
The article is devoted to the influence of microbiological derived proteases on the functional and technological characteristics of meat-based semi-finished products, which included in their recipes the fillets of broiler chickens, chickpeas and lentils. Optimal modes of hydration and pre-treatment of plant raw materials have been established for further enzymatic treatment with Aspergillus niger proteases. Thus, the experimental samples presented semi-finished products with different content of vegetable and meat raw materials, which resulted in the determination of the optimal formulation and its comparison with the data obtained by modeling the formulation by chemical composition and nutritional value. Cтаття присвячена впливу мікробіологічних похідних протеаз на функціональні та технологічні характеристики напівфабрикатів на м’ясній основі, що включають у свої рецепти філе курчат-бройлерів, нут та сочевицю. Встановлені оптимальні режими гідратації та попередньої обробки рослинної сировини для подальшої ферментативної обробки протеазами Aspergillus niger. Таким чином, на експериментальних зразках були представлені напівфабрикати з різним вмістом рослинної та м’ясної сировини, що призвело до визначення оптимальної рецептури та її порівняння з даними, отриманими при моделюванні рецептури за хімічним складом та харчовою цінністю.
Keywords: optimization; meat products; supplements; оптимізація; м’ясні продукти; добавки; кафедра технології м’яса і м’ясних продуктів